New naphthalene-degrading marine Pseudomonas strains. - García-Valdés, E (1988)
Over 100 strains that utilized naphthalene as the only carbon and energy source were isolated from samples of marine sediments taken from a heavily polluted area. The isolates were characterized taxonomically and physiologically. Most of these strains belonged to the genus Pseudomonas, and seven of them did not fit any previous taxonomic description. They differed from type strains in a few biochemical characteristics and in the utilization of aromatic compounds. None had catechol 1,2-dioxygenase activity, and catechol 2,3-dioxygenase was responsible for the aromatic ring cleavage. DNA hybridization demonstrated a close relationship between two isolates and the Pseudomonas stutzeri type strain, and between five isolates and the Pseudomonas testosteroni type strain. On the basis of nutritional and enzymatic characteristics, it was assumed that the seven isolates represent new biovars belonging to the species P. testosteroni and P. stutzeri that are able to degrade aromatic hydrocarbons.